The Effect of Competitive Advertising Interference on Sales for Packaged Goods - Bonfrer, Andre (Institutional Knowledge at Singapore Management University, 2004)
Competitive advertising interference arises when viewers of advertising for a focal brand are also exposed to advertising messages for competing brands within a short time period, say one week for TV advertising. Although competitive advertising interference has been shown to reduce ad recall and recognition and brand evaluation measures, no studies have examined the impact on sales. In this research we use a market response model of sales for two grocery categories in the Chicago area to investigate possible advertising interference effects. The results show that competitive interference effects are strong. When one or more competing brands advertise in the same week as the focal brand, the advertising elasticity diminishes for the focal brand. The rate of decrease depends on the number of competing brands advertising in a particular week and their total GRPs broadcast. We are able to derive optimal advertising levels for the brands within a category so that they all have the maximum sales response from advertising. It transpires that the current level of television advertising within the two categories is much higher than this optimum level, indicating that these grocery brands are likely to be over advertising at present. Curtailing advertising for all the brands would increase the response to advertising for each of them.